The care, a view from health care professionals, as patient family members - Olga Cecilia Wilches Flórez; Angela María Wilches Flórez (Revista Colombiana de Bioética, 2016)
Purpose: reflect on nursing practice, specifically on care, with the purpose of creating questions as an evaluation and auto evaluation for nursing professionals. Methods: A review of documents, taking concepts of renowned authors, is conducted and related ethical aspects concepts in nursing practice and ethical concepts of care and nursing knowledge patterns is developed; all this is argued from the theoretical but always correlating with the reality experienced by the family members of the health service. Conclusions: within the context of nursing it is noticeable that the true meaning of caring is lost, therefore the performance of the professionals in the area is not consistent with the ethical concepts and constructs that are implicit in their performance.